2020
DOI: 10.1088/1757-899x/776/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

The impact of DCSBD plasma discharge on polypropylene

Abstract: The diffuse coplanar surface barrier plasma discharge (DCSBD) still belongs to specific methods of modifying (activating) the surface of polymeric materials. The present work deals with surface treatment of polypropylene foils by plasma discharge, investigation and subsequent identification of changes caused by mentioned discharge. The modified surface was examined by measuring the wetting angle. Film surface morphology and topography was investigated by scanning electron microscope (SEM) and atomic force micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In plasma unmodified PVC polymer films, the glass transition temperatures increase in order from the E (54.5 • C), through the Loss modulus (E ) (64.4 • C) to the temperatures for Tan δ (72.5 • C). Such a sequence of increasing the glass transition temperatures across the modules of dynamic mechanical analysis is thus, in accordance with the literature [70][71][72][73][74] and the same order was recorded even after DCSBD plasma modification, specifically 56.1 • C, 63.9 • C and 72.9 • C, respectively (Table 4). The average change in the glass transition temperature for the plasma modified PVC polymer film was an increase of 1.6 • C for the E , a decrease of 0.5 • C for the E and an increase of 0.5 • C for the Tan δ glass transition temperature (Figure 19).…”
supporting
confidence: 91%
“…In plasma unmodified PVC polymer films, the glass transition temperatures increase in order from the E (54.5 • C), through the Loss modulus (E ) (64.4 • C) to the temperatures for Tan δ (72.5 • C). Such a sequence of increasing the glass transition temperatures across the modules of dynamic mechanical analysis is thus, in accordance with the literature [70][71][72][73][74] and the same order was recorded even after DCSBD plasma modification, specifically 56.1 • C, 63.9 • C and 72.9 • C, respectively (Table 4). The average change in the glass transition temperature for the plasma modified PVC polymer film was an increase of 1.6 • C for the E , a decrease of 0.5 • C for the E and an increase of 0.5 • C for the Tan δ glass transition temperature (Figure 19).…”
supporting
confidence: 91%
“…Additionally, the droplets were enlarged due to merging after DCSBD treatment (up to 5 µm in diameter) in comparison to VDBD. A recent study by Janík et al [ 16 ] demonstrated the formation of very similar structures after the treatment of PP specimens by coplanar DCSBD. However, in both mentioned studies, the size of droplets formed after treatment by DCSBD plasma was around 1–5 µm, which is much higher than our droplets possessing size in nanometers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our recent study considering the surface changes of PA 6 after DCSBD plasma treatment demonstrated the high potential of this technology to be part of industrial systems due to its very fast surface activation (0.25 s) and long-term preservation of the achieved properties [ 7 ]. The largest group of produced polymers worldwide represented by polyolefins were subjected to DCSBD plasma treatment in several studies [ 15 , 16 , 17 ]. However, the used exposure times were often too long (30–60 s) to meet industrial demand.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma source operating in diffuse coplanar surface barrier discharge (DCSBD) represents a suitable and environmentally friendly technique but remains an active way of materials treatment. Plasma based on the DCSBD discharge is one of the non-isothermal atmospheric pressure plasma [1] sources often used for treatment of dif-ferent types of materials such as glass [2,3], films [4], biomaterials [5][6][7][8] and fibers, but also finds an objective application in treatment of polymeric material surface [9], while enables the treatment at large surface areas, according to the electrode dimensions within high speed of process and still maintains producing homogenous in-line source of plasma [10][11][12][13][14]. In the last few years, the plasma working at the atmospheric pressure is more preferred than low pressure plasma, due to its easier industrialization and faster plasma-chemical processes [3,15].…”
Section: Wpływ Niskotemperaturowej Obróbki Plazmowej Na Właściwości Gumymentioning
confidence: 99%